Penerapan Metode Drill And Practice Dalam Menghafal Doa-Doa Wudhu Di DTA Nurun Ni’mah - Alvia Hairunisa; maman abdurahman (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2023)
. Along with the emergence of ideas for reforming religious education and with government support, some of these diverse religious education institutions come into contact with programmatic modern classical education methods. Not only do parents play an important role in children's education, but teachers as educators also become an important part in the process of memorizing children's prayers. This study describes the implementation of the drill and practice method in DTA Nurun Ni'mah. The stages of implementing the drill and practice method at DTA Nurun Ni'mah are the preparation stage, the implementation stage, and the learning evaluation stage. The results showed that the drill and practice method had a significant impact on students' memorization results, although not all students were able to memorize well. But the application of this method helps teachers to more easily carry out the learning process of memorizing prayers. The advantage of the drill and practice method applied at dta nurun ni'mah is that it helps strengthen students' long-term memory, provides continuous repetition of the material or skills being learned. While the weakness is that students only memorize or repeat without really understanding the underlying concepts or principles, and cause boredom in students.